Pretreatment with Pectoral Nerve Block II Is Effective for Reducing Pain in Patients Undergoing Thoracoscopic Lobectomy: A Randomized, Double-Blind, Placebo-Controlled Trial. (17th April 2021) - Luo, Ge; Zhu, Jianjun; Ni, Huadong; Zhou, Qinghe; Lu, Yaping; Shen, Qihong; Yao, Yibing; He, Qiuli; Fu, Jie; Yao, Ming
Abstract : Background . Although video-assisted thoracoscopy has a smaller incision than traditional surgery, the postoperative pain is still severe. Ultrasound-guided pectoral nerve block (PECS) II is a new technique that can reduce pain in patients, and it had not been reported in the analgesia after thoracoscopic lobectomy. Methods . 40 patients scheduled for thoracoscopic lobectomy were randomly divided into two groups. Patients in the PECS II group received 0.5% ropivacaine 25 ml before the general anesthesia, while patients in the placebo group received 0.9% saline. Thirty minutes after the block was performed, a pin-prick test was used to analyze the sense of pain of T2-T6 segments. The primary endpoint was the total consumption of fentanyl. Data were collected in the postanesthesia care unit (PACU) and in the ward within 24 hours after operation. Results . The total consumption of fentanyl and the consumption of fentanyl in the intravenous analgesia pump within 24 hours after the operation were significantly lower in the PECS II group compared to the placebo group (p < 0.05 ). The implementation rate of rescue analgesia during operation and in PACU in the PECS II group was significantly lower than that in the placebo group (p < 0.05 ). The numerical rating scale (NRS) in 1 and 4 h after operation was lower in the PECS II group (p < 0.05 ). Mean arterial pressure (MAP) and heart rate (HR) of the PECS II group at chest entering (T1) were significantly lower than those in the placebo group (p < 0.05 ). Conclusion . Preconditioning of PECS II can stabilize the intraoperative circulation and significantly reduce pain and the consumption of opioids after operation.